Tensile behavior of newly developed undercut anchor in cracked and uncracked concrete - Tomoyuki Hatanaka; Naoki Funaki; Reiji Tanaka; Shogo Fujita (Acta Polytechnica CTU Proceedings)
The authors have been designing a post-installed anchor that fixes itself into concrete material by expanding the anchor tip in an upward direction, and conducted tensile loading tests to confirm its fundamental dynamic characteristics. The test results on three types of test specimens, with anchor morphology as a parameter, indicate that the final failure modes were all anchor bar fractures, and a stable yield strength was confirmed. Additionally, the yield strength characteristics of the proposed anchor in cases where cracks are present on the concrete surface, wherein the anchors are fixed, were experimentally confirmed.